Peran Guru Pendidikan Agama Katolik dalam Pembentukan Komunitas Belajar yang Beriman - Elza Novemiyawati; May Dini Silalahi; Sari Suswati (Sabar : Jurnal Pendidikan Agama Kristen dan Katolik, 2024)
This article explores the role of Catholic religious education teachers in forming a faith-based learning community in schools. Using an educational ethnography approach, this study found that teachers play roles as faith facilitators and agents of social transformation. Through reflective methods and collaborative learning, students are encouraged to live out evangelical values ​​in their daily lives. This article also offers practical strategies for teachers to integrate Catholic values ​​into cross-disciplinary curricula.